A review of Palaeoeskimo dwelling structures in Newfoundland and Labrador - Renouf, M.A. (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2003)
AbstractThis paper reviews and summarizes information about Palaeoeskimo dwelling structures in the Province of Newfoundland and Labrador with the aim of producing a basic resource and research tool. Patterns are noted and some are related to residential mobility.